Technical Efficiency Levels of Rural Banks (BPRs) in West Java: A Stochastic Frontier Approach - Putu Geniki Lavinia Natih (Institute for Economic and Social Research, 2015)
There is considerable evidence from around the world to support the idea that access to formal financial services is a key factor towards achieving poverty alleviation. The government of Indonesia has placed high importance on the issue of improved access to financial services and one feels that it would be appropriate to begin the process of analyzing effective financial inclusion initiatives with the existing Bank Perkreditan Rakyat (BPR) system. BPRs have long been an integral part of Indonesia’s financial, economic, and social development. This research is focused on BPRs in West Java. In this research, the writer evaluates BPR performance within twenty-five districts in West Java, by measuring the technical efficiency levels of the BPRs through employing the Stochastic Frontier Approach (SFA). The district that has the highest BPR average inefficiency score is Bandung city and the district with the lowest average BPR inefficiency score is the district of Ciamis. Increases in bank concentration (indicated by the Hirschman-Herfindahl Index) and income per capita are shown to decrease BPR inefficiency levels. Increases in the percentage of the population under the poverty line, the percentage of the labor force with a high school education, the percentage of road length per area, and the amount of bank offices per district, increase the inefficiency levels of BPRs. Overall, it is found that BPRs cannot operate efficiently in areas which are too underdeveloped; neither can they operate efficiently in areas which are too well developed.AbstrakTerdapat bukti substantif pengalaman berbagai negara di dunia bahwa akses pada jasa finansial formal adalah faktor kunci dalam upaya pengentasan kemiskinan. Pemerintah Republik Indonesia telah menempatkan upaya peningkatan mutu dan akses jasa finansial bagi masyarakat Indonesia, sebagai salah satu kebijakan utama dalam pengentasan kemiskinan. Tulisan ini bertujuan untuk membahas dan menganalisa efektivitas badan-badan penyedia jasa finansial di Indonesia, sebagai starting-point dengan memulai analisa efektivitas jasa finansial yang diberikan oleh Bank Perkreditan Rakyat (BPR). Penelitian ini difokuskan kepada BPR di Jawa Barat. Penulis mengevaluasi performa BPR pada 25 kabupaten/kota di Jawa Barat, dengan mengukur tingkat efisiensi teknis melalui metode Stochastic Frontier Approach (SFA). Kota tempat BPR yang memiliki rata-rata in-efisiensi tertinggi adalah Kota Bandung dan Kabupaten dengan in-efisiensi rata-rata BPR-nya yang terendah adalah Kabupaten Ciamis. Peningkatan dalam konsentrasi perbankan di sebuah kabupaten/kota (terindikasi Hirschman-Herfindahl Index) dan peningkatan pendapatan per kapita pada kabupaten/kota tersebut terbukti menurunkan tingkat inefisiensi BPR. Sebagai kesimpulan utama, ditemukan bahwa BPR tidak dapat beroperasi secara efektif pada area yang sangat underdeveloped dan juga tidak dapat beroperasi efektif pada area yang sangat developed. Kata kunci: Bank Perkreditan Rakyat (BPR); Jawa Barat; Efisiensi Teknis; Stochastic Frontier Approach (SFA)JEL classifications: D; L1; L2; G; G2